2006
DOI: 10.1080/07481180500493443
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Chinese Suicide Attempters: An Emergency Room Study

Abstract: Studying the characteristics of attempted suicide is helpful in knowing the background of some completed suicides and improving prevention or intervention strategies. This current study analyzed data of 74 suicide attempters and 92 accident injured patients admitted to 6 hospital emergency rooms in an area of North-eastern China and found both similarities and differences between Chinese and Western suicide attempters. The data show that more women than men attempted suicide. Perhaps because of the unavailabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
4
21
3
1
Order By: Relevance
“…4 Poverty is increasingly understood by researchers to be more than simply a lack of resource or income, and can include cultural, social, and environmental dimensions, such as shame 70 and religious beliefs. 65 Second, publication bias may have hindered the results, with studies reporting negative and null results being less likely to be published. Third, the exclusion of qualitative studies may have limited understanding of how the experience of poverty may be related to SIB, and the role of cultural, social and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Poverty is increasingly understood by researchers to be more than simply a lack of resource or income, and can include cultural, social, and environmental dimensions, such as shame 70 and religious beliefs. 65 Second, publication bias may have hindered the results, with studies reporting negative and null results being less likely to be published. Third, the exclusion of qualitative studies may have limited understanding of how the experience of poverty may be related to SIB, and the role of cultural, social and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, where multivariate analysis was performed in two Indian studies, only null associations were found for value of livestock and value of agricultural produce amongst farmers 61 and for monthly household income. 56 Of the eleven studies on non-fatal SIB, six 35,41,42,48,57,65 using bivariate analysis reported a positive association and four 37,55,57,58 a null association. However, all studies 34,37,38,41,48,57,64 performing multivariate analysis found a positive association except one 34 which found a null association between perceived financial status and suicide attempts in China.…”
Section: Economic Status and Wealthmentioning
confidence: 98%
See 1 more Smart Citation
“…Suicide risk was found to increase among children and adolescents in inpatient settings when they perceive their family systems as rigid, less adaptable to change, lacking problem-solving skills, and possessing less effective styles of communication (Adams et al 1994). Inpatient populations were reportedly more depressed and anxious when familial self-disclosure was lower (Horesh and Apter 2006), family systems were less supportive (Zhang et al 2006), and exhibited hostile and conflictual interactions (Gunter et al 1999). The qualitative study of Bartimole (2009) found evidence from teens who survived suicide attempts that being loved and valued by their families played a significant role in turning their direction away from suicide.…”
mentioning
confidence: 94%
“…A recent interview study found that Chinese women with prior self-harm perceived more gender inequality than women without prior self-harm behavior (Zhang, Jia, Jiang, & Sun, 2006). A surge of feminist activities following the 1996 Fourth World Conference on Women in Beijing led to major reforms of the China Marriage Law in 2001, including the prohibition of violence between husband and wife (Article 3), and the granting of immediate divorce (Article 31) and financial compensation to victims of spousal violence (Article 46).…”
mentioning
confidence: 99%